Creative Economy: how the interface of Uber Eats and iFood could change your menu - Monty, Renata Cristina da Silva (Brazilian Journal of Operations & Production Management, 2018)
The objective of this paper is to analyze the impact of Creative Economy to customers of food apps in Brazil. In the first part, it is described how cultural products regarding food and cooking in Brazil work. In the second part, a descriptive analysis of the apps iFood and UberEats is proposed in order to understand how the materiality of these products, as an interface, could influence the choice of the menu. For this, food is regarded as a cultural good. The concept immortalized by Marshall McLuhan "the medium is the message" assists us in the descriptive exercise of verifying how information and communication technologies (TICs) affect the experience of eating in the contemporary world. From this point of view, a comparative exercise regarding the materiality of the applications is proposed.